1990
DOI: 10.1007/bf02427835
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord ganglioglioma presenting as hydrocephalus

Abstract: We report a case of a 5 year old boy with a spinal cord ganglioglioma and hydrocephalus. The insidious onset with back stiffness and hamstring tightness, the diagnosis by magnetic resonance imaging, and the treatment by total excision is described. An adequate proven explanation for the hydrocephalus is lacking. Mechanisms which have been proposed include impaired cerebrospinal fluid absorption from increased cerebrospinal fluid protein, and arachnoiditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…(Kalyan-Raman & Olivero 1987;Miller et al 1990b;Zhang et al 2008). Most patients are <30 years old, and the peak age of incidence is the second decade of life (Safavi-Abbasi et al 2007).…”
mentioning
confidence: 99%
“…(Kalyan-Raman & Olivero 1987;Miller et al 1990b;Zhang et al 2008). Most patients are <30 years old, and the peak age of incidence is the second decade of life (Safavi-Abbasi et al 2007).…”
mentioning
confidence: 99%
“…Reported spinal tumors with hydrocephalus are intramedullary, intradural and extradural neoplasms [6]. The most frequent association is with low-grade intramedullary astrocytoma [1,2,8], but other reported spinal neoplasms included anaplastic astrocytomas [13], gangliogliomas [11], neurinomas [12], malignant schwanomas [15], ependymomas [8,12], granulomas [12]. Rifkinson et al [2], reported a series of 25 (15 %) patients, mostly children that developed symptomatic hydrocephalus, from an original series of 171 spinal tumors; of them, thirteen patients had malignant tumors, complicated by increased intracranial pressure with hydrocephalus; of the remaining, 12 developed symptomatic hydrocephalus, after diagnosis of benign spinal tumors.…”
Section: Spinal Tumors and Hydrocephalusmentioning
confidence: 99%
“…Intramedullary tumors of the spinal cord in childhood are usually of low grade [1,2] and are frequently found in the cervical [3,4] and cervicothoracic regions [2,5,6]. They present with symptoms and signs of spinal cord tumor [1,2,4,[6][7][8][9][10][11]. In rare cases intraspinal tumors can manifest at first with hydrocephalus without a spinal cord syndrome [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they may occur anywhere in the brain, preferred sites are the cerebral hemispheres, the floor of the third ventricle, the brain stem, and the cerebellum [9,22]. They occur least commonly in the spinal cord, and especialy rarely in the conus medullaris [16,19,25]. Inthe spinal cord, the most common location is an extention from the medulla into the cervical cord [7,11,17,18,25].…”
Section: Introductionmentioning
confidence: 99%